In vitro degradation of non-starch polysaccharide residues in the digesta of broilers offered wheat-soy or maize-soy diets by feed enzymes - E. Kim; N.K. Morgan; A.F. Moss; A. Solbak; L. Li; P. Ader; M. Choct (Journal of Applied Animal Nutrition)
The present study evaluated the in vitro efficacy of different feed enzymes on degrading non-starch polysaccharide (NSP) residues present in digesta collected from broilers’ gastrointestinal tract. Two dietary treatments, wheat-soy or maize-soy based diets, were assigned to broilers (12 replicates per treatment; 10 birds per replicate pen) from d 0 to 35. At 35 d of age, digesta was collected from the gizzard, jejunum and ileum from three birds per replicate and pooled. The digesta samples were digested in vitro with one of nine enzymes; GH10, GH11 and GH8 xylanase, arabinofuranosidase, a combination of GH10 xylanase and β-glucanase (XYN+BG), β-mannanase, protease, cellulase cocktail and pectate lyase. When using the gizzard digesta as substrate, GH8 xylanase reduced (P<0.005) both insoluble and soluble NSP levels compared to the control, regardless of diet type. Analysis of NSP degradation in jejunal digesta from birds fed the wheat-soy diet revealed that the three xylanases and arabinofuranosidase reduced (P<0.001) insoluble NSP level compared to the control, but the soluble NSP level was not affected by the enzyme treatments. All enzymes, except the cellulase cocktail and pectate lyase, reduced (P=0.005) the insoluble NSP level in the jejunal digesta collected from birds fed the maize-soy diet. Similarly, all enzyme preparations reduced (P<0.001) the insoluble NSP level in ileal digesta obtained from birds fed the maize-soy diet. The GH10 and GH11 xylanase, XYN+BG, cellulase cocktail and pectate lyase reduced (P<0.001) the insoluble NSP level in the ileal digesta from birds fed the wheat-soy diet compared to the control, with XYN+BG exhibiting the greatest reduction. Collectively, the present in vitro study indicated that the in vitro efficacy of enzyme preparations was dictated by the amount and type of NSP remaining undigested in various parts of the gut, which perhaps affect the in vivo efficacy.